Intestinally Secreted C-Type Lectin Reg3b Attenuates Salmonellosis but Not Listeriosis in Mice - van Ampting, Marleen T. J. (American Society for Microbiology, 2012)
The Reg3 protein family, including the human member designated pancreatitis-associated protein (PAP), consists of secreted proteins that contain a C-type lectin domain involved in carbohydrate binding. They are expressed by intestinal epithelial cells. Colonization of germ-free mice and intestinal infection with pathogens increase the expression of Reg3g and Reg3b in the murine ileum. Reg3g is directly bactericidal for Gram-positive bacteria, but the exact role of Reg3b in bacterial infections is unknown. To investigate the possible protective role of Reg3b in intestinal infection, Reg3b knockout (Reg3b(−/−)) mice and wild-type (WT) mice were orally infected with Gram-negative Salmonella enteritidis or Gram-positive Listeria monocytogenes. At day 2 after oral Listeria infection and at day 4 after oral Salmonella infection, mice were sacrificed to collect intestinal and other tissues for pathogen quantification. Protein expression of Reg3b and Reg3g was determined in intestinal mucosal scrapings of infected and noninfected mice. In addition, ex vivo binding of ileal mucosal Reg3b to Listeria and Salmonella was investigated. Whereas recovery of Salmonella or Listeria from feces of Reg3b(−/−) mice did not differ from that from feces of WT mice, significantly higher numbers of viable Salmonella, but not Listeria, bacteria were recovered from the colon, mesenteric lymph nodes, spleen, and liver of the Reg3b(−/−) mice than from those of WT mice. Mucosal Reg3b binds to both bacterial pathogens and may interfere with their mode of action. Reg3b plays a protective role against intestinal translocation of the Gram-negative bacterium S. enteritidis in mice but not against the Gram-positive bacterium L. monocytogenes.